Anatomical Variations of Cystic Ducts in Magnetic Resonance Cholangiopancreatography and Clinical Implications - Radha Sarawagi; Shyam Sundar; Sanjeev K. Gupta; Sameer Raghuwanshi (Radiology Research and Practice)
Background. Anatomical variations of cystic duct (CD) are frequently unrecognized. It is important to be aware of these variations prior to any surgical, percutaneous, or endoscopic intervention procedures. Objectives. The purpose of our study was to demonstrate the imaging features of CD and its variants using magnetic resonance cholangiopancreatography (MRCP) and document their prevalence in our population. Materials and Methods. This study included 198 patients who underwent MRCP due to different indications. Images were evaluated in picture archiving communication system (PACS) and variations of CD were documented. Results. Normal lateral insertion of CD at middle third of common hepatic duct was seen in 51% of cases. Medial insertion was seen in 16% of cases, of which 4% were low medial insertions. Low insertion of CD was noted in 9% of cases. Parallel course of CD was present in 7.5% of cases. High insertion was noted in 6% and short CD in 1% of cases. In 1 case, CD was draining into right hepatic duct. Congenital cystic dilation of CD was noted in one case with evidence of type IV choledochal cyst. Conclusion. Cystic duct variations are common and MRCP is an optimal imaging modality for demonstration of cystic duct anatomy.